1995
DOI: 10.1111/j.1476-5381.1995.tb13246.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a colchicine‐sensitive component of the cytoskeleton for acetylcholine receptor recovery

Abstract: 5 In addition to the normal, large conductance (-48 pS) ACh-activated channels, a population of small conductance (-29 pS) channels was observed in colchicine-treated preparations following exposure to carbachol. In preparations treated with both colchicine and staurosporine and then exposed to carbachol, the conductance of these small channels was identical to that of colchicine or staurosporine alone. 6 We suggest that prolonged exposure of snake twitch fibre endplates to agonist results in the activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We found that m.e.p.c. amplitude recovery is also decreased in muscle preparations treated with colchicine (Hardwick & Parsons, 1995). In the absence of carbachol exposure, m.e.p.c.…”
Section: Discussionmentioning
confidence: 88%
“…We found that m.e.p.c. amplitude recovery is also decreased in muscle preparations treated with colchicine (Hardwick & Parsons, 1995). In the absence of carbachol exposure, m.e.p.c.…”
Section: Discussionmentioning
confidence: 88%
“…We have shown that this cell response to T3 required intact microtubules. Colchicine (lop5 to lop4 M ) was shown to interfere with elements of the cytoskeleton and to alter phosphorylation, which led to poor recovery of acetylcholine receptors in the membrane of snake costocutaneous muscle fibers (19). might interfere with the BAR intracellular trafficking was not confirmed by our study of BAR cell repartition.…”
Section: Discussionmentioning
confidence: 60%
“…Disruption of microtubules by colchicin has been reported to increase conductance of Clchannels in skeletal muscle (21), and decreased conductance of snake twich fibre end plates (20). The mechanism of this functional change and the role of cytoskeletal structures in the transmembrane ion transport is not known.…”
Section: Applications Of Microtubule Inhibitors In Future Researchmentioning
confidence: 99%